Exploring Domains and Elements for Behavioural Competency and Employability Skills - Abd Samad, Noorazman; Wan Ahmad, Wan Mohd Rashid; Sern, Lai Chee; Mohd Noor, Siti Noor Fazelah; Harun, & Hairuddin (Journal of Technical Education and Training, 2018)
Technical Vocational Education Training (TVET) system is crucial in producing skilled workers who can command high incomes, which in turn will help Malaysia achieve the developed nation status by the year 2020. There is a mismatch between the graduates produced by the Public Skills Training Institutes in Malaysia and the competent workforce required by the industry. Therefore, this study aims to explore the domains and elements that can help automotive industry trainees acquire behavioural competence and employability skills. The Delphi technique is used to explore the domains and elements that contribute towards the integration programme for the Public Skills Training Institutes (PTSIs) and Private Training Centres (PTCs)  involved in churning out automotive industry trainees. Analysis of interview data from the two rounds of the Delphi study indicates that 12 domains  contribute to shaping behavioural competence and employability skills, namely governance; framework of qualifications; standard of competence; supplier of skill standards; delivery; industrial relations; experience of industrial work;  twinning programmes;  community service programmes; curriculum-based industrial visits; and educational entrepreneurship.